National and international information policies - Schipper, Wendy ed. (National Federation of Abstracting & Information Services PhiladelphiaUS, 1991)
Features the United States, Canada, Europe, the Asia Pacific Region and the less-developed countries and reveals vastly different views of what is needed in information policy between the have and have-not countries. Discusses current development of information policies in the areas of copyright, standards licensing, telecommunications, government policies, regional politics and the role of the private sector. Looks at issues such as the need for information policy and the resistance to controlling the flow of information.